Investigating the effects of a randomized, double-blinded aerobic, resistance, and cognitive training clinical trial on neurocognitive function in older adults with cardiovascular risk factors: the ACTIONcardioRisk protocol - Louis Bherer; Louis Bherer; Louis Bherer; Tudor Vrinceanu; Emma Gabrielle Dupuy; Emma Gabrielle Dupuy; Mathieu Gayda; Thomas Vincent; Pierre-Olivier Magnan; Pierre-Olivier Magnan; Hanieh Mohammadi; Claudine Gauthier; et al. (Frontiers in Aging Neuroscience)
BackgroundLifestyle factors like exercise and cognitive stimulation might help improve cognitive performance in older adults. However, studies investigating this, reported mixed results. Most of the data supporting the benefit of exercise comes from cross-sectional studies, cohort studies, or short intervention studies of 3–6 months with poorly designed control groups. Meta-analyses suggest that longer intervention studies of around 1 year are more likely to show cognitive improvements and changes in brain biomarkers. Moreover, the type and content and optimal dose of the training program that best predict improvement in cognition is still poorly understood. Latest studies suggest that combining cognitive training with exercise training might have an added benefit. Moreover, functional and structural cerebral mechanisms involved are still poorly documented. Finally, few studies have systematically investigated the potential impact that cardiovascular risk factors (CVRF) progression might have on training neurocognitive outcomes.Methods159 seniors over the age of 60 with CVRF and no contraindications to exercise will be assigned to one of the three 1-year training programs: (1) Physical exercise intervention (aerobic and resistance exercises); (2) Multidomain intervention (combined cognitive training with aerobic and resistance exercises); or (3) Active control (stretching and toning exercises). All interventions take place 3 times a week, are supervised and individualized to each participant’s profile. Assessments will be administered before, half-way and after the intervention: cognition (primary outcome), cerebral imaging with a focus on cerebrovascular mechanisms (secondary outcomes), and exploratory outcomes (genetic profile, chronic stress biomarkers, metabolic function, inflammation markers, mood, sleep, and diet).DiscussionThe present design uses a 12-month intervention period to maximize the likelihood of identifying the cerebrovascular markers involved in exercise training effects on cognitive performance in individuals with CVRF. Moreover, we measure a series of exploratory outcomes that could also play a role in modulating the effect of the multidomain training on cognition. This will allow an investigation of their potential mediating role on the primary outcomes.Clinical trial registration[https://clinicaltrials.gov/] identifier [NCT04962061].